CYBERSECURITY CHALLENGES IN THE ERA OF CLOUD COMPUTING - Anarbayev Sardorbek Odil o'g'li; Eshonqulov Oybek Shuhrat oʻgʻli; Bahronov Shahzodjon Vahobjon oʻgʻli (TADQIQOTLAR, 2025)
Abstract: Cloud computing technology is one of the modern solutions that brought about revolutionary changes in the field of Information Technology. With this technology, users and organizations will be able to store, process and manage their data on remote servers. One of the main advantages of cloud computing is the efficient allocation of resources, reducing costs and providing free access to data at any time, from anywhere. At the same time, with the development of cloud computing technology, new problems and threats are emerging in the field of cyber security. This article will analyze in detail the problems of cyber security that occur during the cloud computing period.